ARTS AND CRAFTS FOR AFRICANS by J. W. Grossert, MA. (Fine Arts), (Organiser of Arts and Crafts, Department of Native Education, Natal). Shuter and Shooter, Pietermaritzburg, 150 pp. - Bubole, H. (International Library of African Music, 1954)
pages: 91
Keywords: African Music